Intervensi Aromaterapi Sereh untuk Menurunkan Tingkat Stress Lanjut Usia - Ningrum, Wanda Anggun Frasetiya; Sukmawati, Anastasia Suci; Suwarno (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Stress is one of the psychological problems frequently experienced by the elderly due to physical, social, and emotional changes associated with aging. High stress levels can reduce quality of life and increase the risk of physical and mental health problems. One of the non-pharmacological methods to reduce stress is lemongrass aromatherapy (Cymbopogon citratus), which contains citral and geraniol compounds known for their calming effects and ability to lower cortisol levels. Objective: To determine the effect of lemongrass aromatherapy on stress levels among the elderly at BPSTW Yogyakarta Unit Budi Luhur. Method: The study used a pre-experimental one group pre-test post-test design. The population consisted of 80 elderly residents, with 57 respondents selected using stratified random sampling. The instrument used was the DASS-42 questionnaire to measure stress levels before and after the intervention. The intervention was conducted using lemongrass aromatherapy via a reed diffuser twice daily for two weeks. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Before the intervention, most respondents experienced moderate stress with an average score of 16.7. After the intervention, stress levels decreased to mild with an average score of 11.4. The Wilcoxon test showed a p-value of 0.001 (<0.05), indicating a significant effect of lemongrass aromatherapy on reducing stress levels among the elderly. Conclusion: Lemongrass aromatherapy has a significant effect on reducing stress levels among the elderly at BPSTW Yogyakarta Unit Budi Luhur. It can be used as a complementary non-pharmacological therapy to promote relaxation and improve psychological well-being in older adults.